If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -3 = 8x + -4 Reorder the terms: -3 + 3y = 8x + -4 Reorder the terms: -3 + 3y = -4 + 8x Solving -3 + 3y = -4 + 8x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3y = -4 + 3 + 8x Combine like terms: -3 + 3 = 0 0 + 3y = -4 + 3 + 8x 3y = -4 + 3 + 8x Combine like terms: -4 + 3 = -1 3y = -1 + 8x Divide each side by '3'. y = -0.3333333333 + 2.666666667x Simplifying y = -0.3333333333 + 2.666666667x
| Y=-5x^2-2x+2 | | 3x-2=3(y-2) | | n/3-4.6=21.6 | | 10-2x^2=-98 | | 12:18/7 | | 2(2x+3)=5x-5 | | 3x+2y+3z=2 | | 2.4=108 | | X^5=4+3logx | | z=1.95 | | 12/1:18/7 | | m+3=2m-1 | | 7/8=3/x-6 | | 3x-2+y-2=60 | | -3x=-12+-10 | | 4(6t+4)=4(5t-5) | | 6r-(r+3)=10-(7-5r) | | 7v/8=21 | | X/4-x/12=2 | | 2x-y+z=-11 | | -1+2x=28+13 | | t/6-2=11 | | kx-3=5 | | u/7=17.92 | | P=344x-560 | | 8v=20.40 | | 3n+8+12n-5-7n+11= | | X-11/2=9 | | 7x=2/3 | | 8/1=.22/n | | 1/7(-21x-2) | | 3x+88=14x |